The Implementation Of Gist Strategy To Teach Reading Comprehension In Senior High School - Selvilya Anggara (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
In order to teach students in reading comprehension, the teachers should choose the right way to achieve their goal in students’ reading achievement by understanding content of the text well. The main purpose of reading is to find the main idea of what the students have read, to create their critical thinking in reading, also to write their own summary towards reading text. Therefore, by using the suitable strategy while teaching and learning processes, it is believed that it would help the students to enhance their reading comprehension. Then, GIST strategy is a learning strategy to teach students in comprehending a reading text that suitable for the students while teaching and learning processes. On the other hand, the purpose of this study is to find out the implementation of GIST strategy and the result after using GIST strategy during teaching and learning processes. The data of this study were gained through observation toward 36 participants of senior high school students in one of school in Tuban. The result showed that the implementation of GIST strategy in explanation reading text help the students in comprehending explanation reading text well. It can be seen in the student’s reading task result as the result after applying GIST strategy and it was analyzed by using ESL Composition Profile considering that the task was in the form of summary based on their own words towards the reading text.